Multidisciplinary shock team is associated with improved outcomes in patients undergoing ECPR. Issue 5 (May 2021) - Hryniewicz, Katarzyna; Hart, Michael; Raile, David; Wang, Yale; Mooney, Michael; Mudy, Karol; Eckman, Peter M; Samara, Michael A; Traverse, Jay; Sun, Benjamin; Williams, David M; Wilson, Kelly J; et al.
Objectives: Veno-arterial extracorporeal membrane oxygenation (VA ECMO) has been increasingly used in cardiopulmonary resuscitation (ECPR) in select patients. Few centers have published their experience or outcomes with ECPR. The aim of our study was to evaluate outcomes of adult patients in cardiac arrest placed on VA ECMO in the catheterization laboratory. Methods: We performed a retrospective analysis of adult patients in refractory cardiac arrest who underwent ECPR at the Minneapolis Heart Institute (MHI) at Abbott Northwestern Hospital from January 2012 to December 2017. Relevant data were obtained from electronic medical records, including arrest to ECMO flow time, total ECMO support time, and outcomes. Results: Twenty-six adult patients underwent ECPR at the study site during the defined time period. Seven patients (27%) sustained cardiac arrest out of hospital, 19 patients arrested in-hospital with eight of those occurring in the catheterization laboratory. Seventeen (65%) patients had initial rhythm of ventricular fibrillation or tachycardia (VF/VT). All patients underwent mechanical CPR with LUCAS device. Overall 30 day and 6 month survival was 69%. Median time from arrest to ECMO flow was 46 mins (21, 68) vs 61 mins (36, 71) in survivors and non-survivors, respectively. Sixteen of 18 survivors discharged with a CPC score of 1 or 2. Conclusions: We demonstrate that adult patients in cardiac arrest initiated on VA ECMO in the cardiac catheterization laboratory and cared for by a multidisciplinary shock team in the critical care unit have superior long-term survival and functionally favorable neurologic recovery when compared to current literature.